Some Significant Issues Related to Conduct of Due Diligence on the Example of Georgian and German Law - Kavtaradze, Salome (Journal of Law, 2020)
Mergers and Acquisitions are very important part of business transactions for many companies. Besides, transactions are unavoidable due to economic changes. There are plenty of methods to ensure successfulness of transactions, but among the Due Diligence Investigation has significant place. Due Diligence is an instrument, which gives possibility to buyer to analyze targeted company fully, to discover strengths and weaknesses of the company, to set real price and etc. As a result, interested company can make decision based on objective and real facts. Due Diligence, as an instrument to analyze companies is broadly used all over the world. Although, despite of frequency of conducting different types of Due Diligence, there is always a dispute if interested party has a legal obligation to conduct Due Diligence before merging or acquiring a company, or on the other side, is Target Company obliged to let them conduct Due Diligence, as most sensitive information’s are subject of analyzing. It’s important to look at Due Diligence also as well-known commercial custom, as in some countries Due Diligence is considered to be commercial custom There are lot of issues regarding legal or procedural conduct of Due Diligence, but in the given paper will be discussed legal on non-legal obligation of conduction Due Diligence on behalf of Georgian and German Law.